Structure characteristics and microwave dielectric properties of ZnZrNb2O8 oxide ceramics - Kumar, Ashwini; Sharma, Poorva; Qiu, Fujun (Frontiers in Materials, 2024)
This study investigates the synthesis, structural analysis, and microwave dielectric characteristics of ZnZrNb2O8 ceramics, prepared via solid-state reaction method and subjected to sintering at temperatures ranging from 1000 to 1200 °C for 4 hours. X-ray diffraction (XRD) analysis confirms the successful formation of ZnZrNb2O8 phase, with a monoclinic wolframite phase. Scanning electron microscopy (SEM) investigations unveil microstructural features such as grain size and porosity, reveals material's morphological details. Dielectric properties conducted in the microwave frequency regime show a correlation between dielectric constant (r) and relative density of the ceramics. Importantly, the ceramics exhibited a suitable dielectric constant and low dielectric loss, indicative of their suitability for microwave applications. Remarkably, ZnZrNb2O8 ceramics sintered at 1150 °C for 4 hours exhibit excellent microwave dielectric properties (r = 27.2, Q  f = 54,500 GHz, and τf = -60 ppm/ C). These findings underscore the potential of ZnZrNb2O8 ceramics as advanced materials for high-frequency applications, including filters, resonators, and other microwave devices, thus contributing significantly to the advancement of next-generation telecommunications technologies.